Designing and evaluating social safety nets: theory, evidence, and policy conclusions - Coady, David (International Food Policy Research Institute, 2004)
Developing countries urgently require a more effective poverty alleviation strategy. The emerging consensus is that renewed broadbased economic growth is a necessary condition for alleviating poverty, but in isolation this is insufficient. Effective social safety nets are also important components of any comprehensive poverty alleviation strategy. Existing social safety nets, however, suffer from shortcomings: they often fail to reach the intended target group, they fail to generate a sustained decrease in poverty, they often involve many uncoordinated or duplicative transfer programs, they can be inefficient and costly, and the transfers are often too small.